Female genital mutilation/cutting: changes and trends in knowledge, attitudes, and practices among health care professionals in The Gambia - Kaplan Marcusán A; Riba Singla L; Laye M; Secka DM; Utzet M; Le Charles MA (Dove Medical Press, 2016)
Adriana Kaplan Marcusán,1–3 Laura Riba Singla,3 Mass Laye,3 Dodou M Secka,3 Mireia Utzet,4 Marie-Alix Le Charles3 1Social Knowledge Transfer/Parc de Recerca UAB – Santander, Universitat Autònoma de Barcelona, Barcelona, Spain; 2Interdisciplinary Group for the Study and Prevention of Harmful Traditional Practices, Department of Social and Cultural Anthropology, Universitat Autònoma de Barcelona, Barcelona, Spain; 3Wassu Gambia Kafo, Fajara F Section, The Gambia; 4Africa and Latin America Research Group, Unit of Biostatistics, Faculty of Medicine, Universitat Autònoma de Barcelona, Barcelona, Spain Background: Female genital mutilation/cutting (FGM/C) is a harmful traditional practice that affects two out of three girls in The Gambia, seriously threatening their life and well-being with severe health consequences. By tracking the reference values established in former research conducted between 2009 and 2011, the objectives of this study are to explore trends and to measure and assess changes in knowledge, attitudes, and practices regarding FGM/C among health care professionals (HCPs) in The Gambia.Methods: A cross-sectional descriptive study was designed to collect and analyze data from an overall stratified sample consisting of 1,288 HCPs including health professionals and students throughout the six regions of The Gambia. Data were collected by the implementation of a self-administered written knowledge, attitudes, and practices questionnaire between 2012 and 2014.Results: The results of this study showed that 76.4% of HCPs are eager to abandon FGM/C, and 71.6% of them regard it as a harmful practice with negative consequences on life and health. HCPs reported more knowledge and favorable attitudes towards FGM/C abandonment, being better able to identify the practice, more aware of its health complications, and more concerned in their essential role as social agents of change. However, 25.4% of HCPs still embraced the continuation of the practice, 24.4% expressed intention of subjecting their own daughters to it, and 10.5% declared to have performed it within their professional praxis.Conclusion: Findings confirm progress in knowledge and attitudes regarding FGM/C among HCPs, who are better skilled to understand and manage the consequences. Nevertheless, discrepancies between information, intention, and behavior unveil resistance in practice and proves that FGM/C medicalization is increasing. Thus, there is an urgent need to support HCPs in the integration of FGM/C preventive interventions within the public health system, to address arguments favoring medicalization, and to use data to design appropriate strategies. Keywords: female genital mutilation/cutting, The Gambia, health care professionals, knowledge, attitudes, practices, changes, trends, sexual and reproductive health